Variation of Soil Microbial Community and Sterilization to Fusarium oxysporum f. sp. niveum Play Roles in Slightly Acidic Electrolyzed Water-Alleviated Watermelon Continuous Cropping Obstacle - Wu, Xue; Wu, Cuinan; Lu, Daipeng; Wu, Yiwen; Ye, Zhangying; Xia, Liru; Sun, Yudong; Bao, Encai; Ye, Lin; Tang, Yuxin; Cao, Kai (Frontiers in Microbiology, 2022)
It is critical to exploit technologies for alleviating watermelon continuous cropping obstacle which frequently occurs and results in the limiting production and economic losses of watermelon. This study aimed to explore the effects of slightly acidic electrolyzed water (SAEW) on watermelon continuous cropping obstacle. The results showed that SAEW significantly improved the growth of watermelon seedlings cultivated in continuous cropping soil and caused a mass of changes to the diversity of soil microbial community. Compared with Con, SAEW decreased the diversity index of bacteria by 2%, 0.48% and 3.16% while increased the diversity index of fungus by 5.68%, 10.78% and 7.54% in Shannon, Chao1 and ACE index, respectively. Besides, the enrichment level of Fusarium oxysporum f. sp. niveum (FON) was remarkably down-regulated by 50.2% at 14 d of SAEW treatment, which could decrease the incidence of Fusarium wilt disease. The wet and dry weights of FON mycelia in fluid medium were depressed more than 93% and the number of FON colony in continuous cropping soil was reduced by 83.56% with SAEW treatment. And a strong correlation between watermelon, FON and SAEW was presented by correlation analysis. Furthermore, the content of endogenous reactive oxygen species (ROS) was over quadruply increased by SAEW, which may contribute to the sterilizing effect of SAEW on FON. Taken together, our findings demonstrated that exogenous SAEW could alter the soil microbial diversity and decrease the accumulation of FON, which improved the growth of watermelon seedlings and finally alleviated continuous cropping obstacles of watermelon.